Enhancing Tourists’ Environmentally Responsible Behavior at Zero-Waste Destinations: The Moderating Role of Environmental Facilitating Conditions - Nihayatu Aslamatis Solekah; Mardiana Mardiana; Hary Saputro Kurniawan (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2026)
Background: Environmental damage caused by visitor waste has become a critical issue, especially at zero-waste tourist sites. Therefore, understanding tourists’ Environmentally Responsible Behavior (ERB) is essential. Purpose: This study aimed to investigate the factors influencing ERB in zero-waste tourism. Method: This quantitative study adopted the Value-Attitude-Behavior (VAB) theory to examine relationships among variables related to tourists’ ERB at zero-waste destinations. Data were purposively collected from 300 tourists of zero-waste destinations in Batu City, East Java. They were then analyzed using structural equation modelling (SEM) with SmartPLS. Findings: The results indicate that environmental concern and environmental knowledge significantly shape tourists’ ERB, while place attachment does not. Both environmental attitude and environmental subjective norm strongly influence ERB. Moderation analysis reveals that the Environmental Facilitating Condition (EFC) significantly strengthens the relationship between environmental attitude and ERB, but not between subjective norm and ERB. Conclusions: This research contributes by integrating VAB theory with EFC as a moderator in the context of zero-waste tourism. It demonstrates that positive environmental attitudes and adequate facilities could significantly build responsible tourist behavior. Meanwhile, emotional attachment to a certain place is less influential. Research implication: These findings suggest that destination managers and policymakers simultaneously enhance environmental awareness and upgrade facilities or support systems. They should invest in both educational interventions and practical infrastructure to promote sustainable behavioral changes towards environmentally responsible tourism.